Comparing the Effects of Face-to-Face and Virtual Self-Care Training Methods on Self‐Care and Quality of Life among Patients with Heart Failure: A Randomized Clinical Trial Study - Mohsen Ahmadi; Khodayar Oshvandi; Leili Tapak; Seyed Kianoosh Hosseini; Azim Azizi (Hamadan University of Medical Sciences, 2023)
Background and Objective: Heart failure is one of the most common chronic, progressive, and debilitating heart disorders, exerting a destructive effect on self-care and quality of life in these patients. The present study aimed to compare the effects of face-to-face and virtual self-care training methods on self‐care and quality of life among patients with heart failure. Materials and Methods: This three-group clinical trial study was conducted on 120 patients with heart failure admitted to Farshchian Hospital in Hamadan. The samples were selected via the available sampling method and assigned to three groups (control, virtual, and face-to-face education) using permuted block randomization. Demographic characteristics form, European Heart Failure Self-care Behaviour Scale (EHFScBs), and Minnesota Living with Heart Failure Questionnaire (MLHFQ) were completed by self-report before the intervention. The control group received only the routine training of the clinic, while the face-to-face training group received self-care training in four one-hour group sessions, one day apart. The virtual group received the same amount of education in the form of educational clips, and two months after the intervention, the questionnaires were completed. Chi-square tests, Fisher's exact test, paired t-test, and one-way analysis of variance were used to analyze the data. Results: The results pointed out that before the intervention, there was no statistically significant difference between the demographic variables, self-care, and quality of life of patients in the three groups (P> 0.05). After the intervention, no statistically significant difference was observed between the virtual and face-to-face training groups in terms of self-care and quality of life (P>0.05). Nonetheless, self-care and quality of life were improved in these two groups compared to the control group (P˂0.05). Conclusion: Both virtual and face-to-face training methods had the same effect on self-care and quality of life. Virtual training is a great alternative to face-to-face training in the absence of necessary conditions.